Bike-sharing systems' impact on modal shift: A case study in Delft, the Netherlands. (20th June 2020) - Ma, Xinwei; Yuan, Yufei; Van Oort, Niels; Hoogendoorn, Serge
Abstract: Bike-sharing systems have witnessed rapid growth in the last decades. Bike-sharing has been found to influence modal shift from car, public transit, and active transportation modes. However, the impacts on modal shift by considering different kinds of bike-sharing systems are rarely discussed. This study examines the modal shift dynamics and the influential factors on modal shift in response to various bike-sharing systems. Data are obtained by an online survey targeting both non-bike-sharing users and bike-sharing users in a Dutch context. Binary logit models are developed to investigate the relationship between modal shift to bike-sharing with socio-demographic, commuting trip and motivation factors. The survey results show that dockless bike-sharing (Mobike) users are more likely to be non-Dutch and often have no driving license, whereas the situation is opposite for docked bike-sharing (OV-fiets), bicycle-lease (Swapfiets) and non-bike-sharing users. Except for train use, bike-sharing users reduced walking, the use of private bicycle, bus/tram and car. Swapfiets showed a most significant influence on modal shift for both single and multimodal trips. The regression model results indicate that "No stolen/damage problem" and "Cheaper than other modes" are significant factors promoting dockless bike-sharing and bicycle-lease. "Good quality of bicycles" is a significant factor considered by docked bike-sharing and bicycle-lease users. "Public transport subsidy by employer" encourages commuters to shift to docked bike-sharing, whereas individuals with a government student discount are less likely to shift to Swapfiets. Male and multimodal commuters are more likely to use dockless bike-sharing. Commuters are less likely to shift to docked bike-sharing if the trips are "Short" or suitable for "Private bicycle". The findings provide a clear understanding of the modal shift and its determinants that can help municipal planning and policy decision-making in terms of bike-sharing systems. Highlights: User characteristics, motivations and modal shift patterns of different bike-sharing systems are revealed. Binary logit models are established to analyze how various determinants influence people's modal shift in commuting trips. Implications are identified to help municipal planning and policy decision-making in terms of bike-sharing systems.